Augusto de Campos e o Labirinto Verbicovisual de Poetamentos - Vasconcelos, Raíra Costa Maia de (2012)
The present work aims to analyze Poetamenos s three poems, Augusto de Campos, thought principles of Culture Semiotic, which support the our theoretical and analytical reflections. Each chapter introduces a study of poem, plus relevant theoretical considerations to our investigation. The first chapter brings an intersemiotic dialogue between the poem lygia fingers and Mondrian s pictorial principals, demonstrating our preoccupation to discuss about the interactions among diverse cultures e traditions. In the second chapter, we have like nodal point of our analysis the poem eis os amantes semiotic intercourse with the oriental ideogram, which served to a different layout of the words in the page area. The third and last chapter explains the study of the poem dias dias dias staffed in the interrelations of this art form with the music, that are introduced thought the Webern s music language.